Misyjny wymiar duchowości Świętej Teresy od Dzieciątka Jezus - Zofia Kaczmarek, (Annales Missiologici Posnanienses, 2019)
Currently, 92 years have passed since the announcement of St. Teresa of the Child Jesus, patron of the mission. There are still questions about the legitimacy of this act made by Pope Pius XI. However, this article focuses primarily on the timeliness of this patronage, and not on the act itself and its legitimacy. First, it presents the missionary life of the Saint of Lisieux, which is a de facto missionary feature of her spirituality, and then the “missionary thought” of Saint. Teresa of the Infant Jesus is juxtaposed with the teaching of the Church, represented by Vatican II and Redemptoris Missio John Paul II.